DESIGN, OPTIMIZATION, AND EVALUATION OF ACYCLOVIR FAST DISSOLVING TABLETS EMPLOYING STACH PHTHALATE – A NOVEL SUPERDISINTEGRANT - SANTOSH KUMAR R; ANNU KUMARI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the present research was to prepare starch phthalate (a novel superdisintegrant) and to optimize and formulate acyclovir fast dissolving tablets employing 23 factorial design using starch phthalate as superdisintegrant. Materials and Methods: Drug excipient compatibility studies such as Fourier-transform infrared spectroscopy, differential scanning calorimetry, and thin-layer chromatography were carried out to check the drug interaction between acyclovir and starch phthalate. The direct compression method was used for tablet preparation. Prepared tablets were then evaluated for hardness, friability, drug content, disintegration time, water absorption, and wetting time, in vitro dissolution studies. Response surface plots and contour plots were also plotted to know the main effects and interaction effects of independent variables (starch phthalate [A], croscarmellose sodium [B], and crospovidone [C] on dependent variables [disintegration time and drug dissolution efficiency in 1 min]) and stability studies were also done. Results: Tablets of all formulations were of good quality concerning drug content (100±5%), hardness (3.6–4.0 kg/cm2), and friability (<0.16%). In all formulations, formulation F8 found to be optimized formulation with least disintegration time 9±3 s, less wetting time 10±0.17 s, and enhanced dissolution rate in 1 min, i.e., 99.92±0.11 as compared to other formulation. Conclusion: From the research, it was concluded that on combination with crospovidone (5%) and croscarmellose sodium (5%), starch phthalate (10%) enhanced the dissolution efficiency of the drug. Hence, starch phthalate can be used as a novel disintegrant in the manufacturing of fast dissolving tablets.